PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES - Agustina, Zuraida Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this level is to find out the influence of financial ratio to the stock return at food and beverages companies which are listed in the Indonesia Stock Exchange. The sample collection technique is carried out by using purposive sampling. The data is obtained from the Indonesia Stock Exchange, from the internet access through www.idx.co.id and from the Indonesia Capital Market Directory (ICMD). The Multiple Linear Regression Analysis is used in this research. The result of the research shows that Current Ratio, Total Assets Turn Over, Debt to Equity Ratio, Return on Assets, and Return on Equity have insignificant influence to the stock return while Price Earnings Ratio has significant influence to the stock return. Keywords: Financial Statement, Investment, Financial Ratio, Stock Return